E-Accounting System / Gan Chaur Chan - Gan, Chaur Chan (2003)
Universal Sdn. Bhd. is a financial company. It ts located in Jalan Teh Ewe Lim, Penang. The aim of this project is to build an e-Accounting system for Universal Sdn. Bhd. to replace its existing system in order to upgrade the businesses. The objectives of this system are to build a web page, to create a user interface, to create electronic forms, to provide bookkeeping services and to develop a database for the e-Accounting system. Documents analysis and observation have been done at Universal Sdn. Bhd. to get a better view of the old system. Waterfall methodology was the chosen methodology to assist in the project development. This system is divided into two modules, i .e. the administrator module and the user module. The functional requirements for the administration module are to upload services, update price rate, retrieve information, authentication and feedback maintenance. Where as, the functional requirements for the user module are to register for non authentication user, login and edit account for authentication user, browsing capabilities and feedback. The non-functional requirements are performance, information, economy, control (and security), efficiency and service The development tools for this system are Active Server Pages (ASP), Microsoft Access, Visual Studio 6.0, Internet Information Server (IIS), Microsoft FrontPage and Windows 2000 Professional. Besides that, the hardware involves are the PC with Pentium II (300 MHz or higher), 128 MB of RAM, at least 1 GB of hard disk space, VGA or higher-resolution monitor; Super VGA recommended and peripherals - Microsoft Mouse or compatible pointing device. To produce the best result, the system is tested to confirm that the objectives of the system are fulfilled and fully operational.